The Challenges and Rewards of Carrying Out Qualitative Research on the Police in the African American Community - Pryce, Daniel K.; Whitaker, Ingrid Phillips (International Journal of Criminology and Sociology, 2024)
In this paper, we discuss the challenges and rewards of carrying out qualitative research on the police in the African American1 community. Using data drawn from interviews with seventy-seven African American adults in Durham, NC, we found that community member hostility toward research(ers) and fear of both neighbors and the police lowered African Americans’ willingness to be interviewed about their perceptions of and experiences with U.S. police. These findings were observed primarily in public housing and middle-income communities. On a positive note, we found that greater awareness of policing issues increased African Americans’ willingness to participate in research about the police. This finding was more common among upper-middle-income African Americans. The implications of our findings for future research and improved policing in the African American community are discussed.